W „ludowym” pułku – Andrzej Galica na czele I Batalionu 4 Pułku Piechoty Legionów Polskich (1915-1916) - Kozłowska, Aleksandra (Zeszyty Wiejskie, 2010)
Andrzej Galica (1873-1945) was born in Biały Dunajec, the village in Podhale region. The future general became the independence activist before 1914. When the World War 1 had started he came from Vienna to Cracow with the group of volunteers. He served in the Polish Legions, first as the commander of the supplementary battalion. In the springtime of 1915 he took a part in forming of the 4th Legionary Infantry Regiment in Rozprza near Piotrków Trybunalski. In the period April 1915-May 1916 Andrzej Galica commanded the 1st battalion of this regiment. He went at the front on the 15th of July 1915. He took a part in the battle of Jastków. It was his baptism of fire. Andrzej Galica was especially related to 4th Legionary Infantry Regiment because a lot of peasants, just like he, served in this unit. In the period June-September 1917 he commanded the whole regiment. Andrzej Galica became the part of the legend of 4th Legionary Infantry Regiment. This true-born highlander was connected to this unit to the end of his life.